Non-Coding RNA in Penile Cancer - Pinho, Jaqueline Diniz; Silva, Gyl Eanes Barros; Teixeira-Júnior, Antonio Augusto Lima; Rocha, Thalita Moura Silva; Batista, Lecildo Lira; de Sousa, Amanda Marques; Calixto, José de Ribamar Rodrigues; Burbano, Rommel Rodrigues; Souza, Carolina Rosal Teixeira de; Khayat, André Salim (Frontiers in Oncology, 2022)
Penile cancer (PC) still presents a health threat for developing countries, in particular Brazil. Despite this, little progress has been made on the study of markers, including molecular ones, that can aid in the correct management of the patient, especially concerning lymphadenectomy. As in other neoplasms, non-coding RNAs (ncRNAs) have been investigated for penile cancer, with emphasis on microRNAs, piRNAs (PIWI-interacting small RNAs), and long non-coding RNAs (LncRNAs). In this context, this review aims to assemble the available knowledge on non-coding RNA linked in PC, contributing to our understanding of the penile carcinogenesis process and addressing their clinical relevance. ncRNAs are part of the novel generation of biomarkers, with high potential for diagnosis and prognosis, orientating the type of treatment. Furthermore, its versatility regarding the use of paraffin samples makes it possible to carry out retrospective studies.